Anticancer Activity of Bee Venom against Lung Cancer Cell Line (A549 Cells) Enhanced by Iron Oxide Nanoparticles Synthesized from Syzygium Aromaticum: Anticancer activity of Bee venom against A549 cells - Bagyalakshmi, Balasubramanian; Lalitha Priyadarshini, Sivamani; Balamurugan, Angusamy (Journal of Drug Delivery and Therapeutics, 2019)
Iron oxide nanoparticles were synthesized using aqueous extracts of Syzygium aromaticum. Total phenolic content and iron oxide nanoparticles were found to increasing with concentration of extract and had higher antioxidant activity. The UV-Visible spectral analysis showed absorption peaks at 240 nm. SEM image of nanoparticles revealed that they were aggregated and had irregular shape. The signals obtained in EDAX spectrum imply that particles synthesized were iron oxide nanoparticles. The FT-IR spectrum revealed that nanoparticles which is capped by C-H group of alkane. The average size of nanoparticles was 52 nm. The nanoparticles were mixed with bee venom in various ratios to enhance anticancer activity and were identified as 1:1. MTT assay of 1:1 volume ratio of iron oxide nanoparticles and bee venom was found to have cytotoxicity higher than absence of nanoparticles. It confirmed the enhancement of anticancer activity by iron oxide nanoparticles of clove extract. Keywords: Syzygium aromaticum; Green synthesis; Iron oxide nanoparticles; Bee venom; Anticancer activity.